Character association and path coefficient studies on yield and its attributes in safflower (Carthamus tinctorius L.): Character association and path coefficient studies on yield and its attributes in safflower (Carthamus tinctorius L.) - M V DHUPPE; D S MUTKULE; A K GHOTMUKALE (Journal of Oilseeds Research, 2020)
Thirty two genotypes were evaluated for the estimation of heritability, correlation, path analysis and genetic divergence for ten yield traits. High estimates of heritability were recorded for all the traits. High heritability coupled with high genetic advance was recorded for plant height, seed yield/plant, number of seeds/capitulum and number of effective capitulum/plant, 100-seed weight and harvest index. The seed weight contributed maximum towards genetic divergence. From the combined results of correlation coefficient and path analysis, it was observed that number of effective capitulum, number of seeds/capitulum, 100-seed weight are the major yield contributing characters to apply selection pressure for improving yield. The genotypes possessing combination of above characters should be used in a breeding programme for obtaining high yielding segregants.